2014
DOI: 10.1101/gad.241588.114
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of insulin and Notch pathway activities by microRNA miR-305 mediates adaptive homeostasis in the intestinal stem cells of the Drosophila gut

Abstract: Homeostasis of the intestine is maintained by dynamic regulation of a pool of intestinal stem cells. The balance between stem cell self-renewal and differentiation is regulated by the Notch and insulin signaling pathways. Dependence on the insulin pathway places the stem cell pool under nutritional control, allowing gut homeostasis to adapt to environmental conditions. Here we present evidence that miR-305 is required for adaptive homeostasis of the gut. miR-305 regulates the Notch and insulin pathways in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 35 publications
2
68
0
Order By: Relevance
“…This probably leads to elevated levels of InR protein in nutrient-deprived cells, which sensitizes them to insulin and thereby ensures a rapid response when growth conditions are restored. Lin-28 might also regulate InR via a 3′UTR mechanism, as it was recently shown that the microRNA miR-305 negatively regulates InR levels in ISCs via its 3′UTR (Foronda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This probably leads to elevated levels of InR protein in nutrient-deprived cells, which sensitizes them to insulin and thereby ensures a rapid response when growth conditions are restored. Lin-28 might also regulate InR via a 3′UTR mechanism, as it was recently shown that the microRNA miR-305 negatively regulates InR levels in ISCs via its 3′UTR (Foronda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 20E is a major regulator of reproductive events PBM; however, its role in regulating digestive enzymes is not understood. Several insect miRNAs have been shown to be regulated by 20E [20][21][22][23][24] and insulin [25][26][27] signaling pathways. Because mature miR-1890 levels are enhanced PBM, we investigated the role of insulin and 20E signaling pathways in regulating miR-1890 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The mir-317 influences reproductive responses by females to male sex peptide (Fricke et al 2014) and was involved in cell cycle control in association with G2/M cyclin B in Drosophila (Pushpavalli et al 2014). miR-305 regulates the Notch and insulin pathways in the intestinal stem cells, which are required for adaptive homeostasis in the Drosophila gut (Foronda et al 2014). mir-2788a plays a potential role in butterfly wing development in Heliconius (Surridge et al 2011).…”
Section: Discussionmentioning
confidence: 99%